Velocity Control Based on Active Disturbance Rejection for Air-Breathing Supersonic Vehicles. (17th May 2018) - Ming, Chao; Sun, Ruisheng; Wang, Xiaoming
Abstract : This paper investigates a velocity tracking control approach for air-breathing supersonic vehicles with uncertainties and external disturbances. Considering angle of attack is difficult to be precisely measured in practice, extended state observer technique is introduced into the state reconstruction design. In order to avoid possible oscillations in the design of the traditional extended state observer (TESO), a modified extended state observer (MESO) is developed, where a new smooth function is proposed to replace nonsmooth function of TESO. On the basis of it, an active disturbance rejection controller (ADRC) is designed for velocity control systems. Simultaneously, the closed-loop stability is rigorously proved by using Lyapunov theory. Finally, numeric simulations are conducted to validate the effectiveness of the proposed method.